An attitude coordination architecture for communications routing in LEO constellations - Platanitis, Konstantinos; Shufflebotham, Alex; Ramavaram, Harish Rao; Persson, Olle; Laufer, Rene; Sabatini, Marco; Upadhyay, Saurabh; Felicetti, Leonard (EUCASS, 2025)
In this work, the challenge of using multiple satellite constellations in LEO for establishing communication links between two ground stations is investigated. Low altitude orbits and limited onboard equipment capabilities, which lead to reduced coverage areas and frequent visibility changes, create a highly dynamic problem. To address typical requirements such as maximising link uptime and/or minimising communication delay, an architecture for optimising the selection of a signal route and attitude control for the involved relay satellites’ attitude is presented herein. This architecture is deterministic and can be distributed among all the involved satellites, allowing them to operate individually towards achieving the desired goal.